Robust Lessons about Practical Early Warning Systems - Katja Sawischlewski; Lukas Menkhoff; Daniela Beckmann (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
Early warning systems (EWSs) are subject to restrictions that apply to exchange rates in general: fundamentals matter but their influence is small and unstable. Keeping this in mind, five lessons emerge : First, EWSs have robust forecasting power and thus help policy-makers to prevent crises. Second, among competing crisis definitions there is one which is most practical. Third, take a logit model to condense information from various fundamental variables. Fourth, add a regional contagion dummy to the standard set of variables. Fifth, one may be tempted to address instability over time and countries by taking shorter samples and regional EWSs.
Keywords: F31; F33; F37; 330; early warning system; currency crises; emerging markets